Assessment of Health Care Quality through Clients’ Perspectives at Outpatient Consultancy Clinics in Al-Hilla City Hospitals - Hamzah, Mahdi; Talib, Mahasin (Iraqi National Journal of Nursing Specialties, 2020)
Objectives: To assess quality of health care for clients at outpatient consultancy clinics in Al-Hilla City Hospitals, and to find out significant differences between the clients' perspectives toward quality of health care dimensions and their demographic characteristics such as (residence, age, gender, level of education, and occupation ). Methodology: A descriptive analytic study design was carried out at outpatient consultancy clinics of Al- Hilla city hospital (Al-Hilla and Al-Imam Al-Sadiq general teaching hospital) from April 10 th to June 15 th 2019. Non – probability (purposive) sample of 200 clients who were coming to the Outpatient Consultancy Clinics were selected. Data is collected through used of an assessment tools and interview technique with (27) items of questionnaire. A pilot study is conducted for the determination of the reliability of the assessment tool through the use of internal consistency reliability through the use of Alpha Cronbach approach(0,85) (p